Changes in cellular energy allocation in Enchytraeus albidus when exposed to dimethoate, atrazine, and carbendazim - Novais, Sara C.
Cellular energy allocation (CEA) is a methodology developed to evaluate the effects of toxic stress on the metabolic balance of organisms. It consists of the integration of the energy reserves available (Ea; total carbohydrate, protein and lipid content) and energy consumption (Ec) estimated by measuring electron transport system (ETS) activity. The main goal of the present study was to evaluate the effects on the energy budget of the soil invertebrate Enchytraeus albidus (Oligochaeta) after exposure to dimethoate, atrazine, and carbendazim (by testing the reproduction 10% effective concentration, 20% effective concentration, 50% effective concentration and 90% effective concentration) over periods of time from 0 d to 2 d, 4 d, and 8 d. Significant changes in energy reserves were observed with all pesticides, together with effects on energy consumption. Carbohydrates were the first energy source to be used, and clear depletions occurred with all pesticides. Energy consumption increased generally over longer exposures and with higher concentrations of the pesticides. Although clear changes were seen in the individual energy reserve budgets and on Ec, CEA was only significantly reduced with atrazine exposures longer than 4 d. The nearly absent effects on CEA at concentrations known to affect reproduction indicate that the reduction in reproduction is not likely to be caused by a reduction in the total energy budget during the first 8 d of exposure. The present study showed the importance of complementing CEA interpretation with the individual Ea and Ec parameters, in particular if these show opposite balances. The Ea and Ec results were in good agreement with gene transcription results from a parallel study, hence suggesting translation and showing the advantage of combining various effect levels to advance the understanding of mechanisms.